2018
DOI: 10.1186/s12875-018-0713-x
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Al Kharj diabetic patients’ perception about diabetes mellitus using revised-illness perception questionnaire (IPQ-R)

Abstract: BackgroundIllness perception questionnaires for various medical conditions have become more useful in recent years. However, very few have addressed this issue for Type 2 diabetes in Saudi Arabia.MethodsA self-administered questionnaire was distributed to Type 2 diabetic patients attendees of primary health care centers and Al Kharj Military Industries Corporation Hospital in Al Kharj, Saudi Arabia, from November 24th 2016 to April 24th, 2017.ResultsOverall, 383 of the 500 distributed questionnaires were retur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
1
3
0
1
Order By: Relevance
“…In the study, participants attributed diabetes causes to heredity or genetic factors passed on through one’s clan and family. Similar observations were reported by Al-Ghamdi [ 40 ] where study participants linked diabetes with heredity. The association of diabetes as an inheritable disease may have implications to public initiatives on prevention and early detection of the disease since people with no history of people with diabetes in the family may believe that they are not at risk of getting it.…”
Section: Discussionsupporting
confidence: 89%
“…In the study, participants attributed diabetes causes to heredity or genetic factors passed on through one’s clan and family. Similar observations were reported by Al-Ghamdi [ 40 ] where study participants linked diabetes with heredity. The association of diabetes as an inheritable disease may have implications to public initiatives on prevention and early detection of the disease since people with no history of people with diabetes in the family may believe that they are not at risk of getting it.…”
Section: Discussionsupporting
confidence: 89%
“…The study (n = 192) of collaborative goals (listen and learn, share ideas, caring relationship, agree on objective, support) between doctor and patients with diabetes showed there to be significant association with increased perceived self-management competence, which was significantly associated with increased self-management behaviors (Morris et al, 2017). In Saudi Arabia, the results of the study (n = 383) showed that diabetic patients need more education programs about how to identify and manage symptoms of disease (Al-Ghamdi et al, 2018). Oliver (1980) expressed that satisfaction is the function of expectation and expectancy disconfirmation, and satisfaction influences attitude change and intention of purchase (Oliver, 1980) and consumers will be satisfied when their assessment of a service or product confirms their expectations (Roig et al, 2013).…”
Section: Theoretical Foundation and Hypothesis Developmentmentioning
confidence: 92%
“…In the Netherlands, patients with T2D in the first year after diagnosis perceived T2D as a chronic, yet relatively controllable condition with minor consequences (van Puffelen et al, ). According to Al‐Ghamdi et al (), the majority of 383 Saudi patients perceived that diabetes was hereditary and attributed to diet/eating habits (75% and 62.4%, respectively). Libyan patients with T2D showed moderately high personal control and treatment control perceptions; however, a large proportion reported a perception of diabetes as a chronic disease (Ashur, Shah, Bosseri, Morisky, & Shamsuddin, ).…”
Section: Introductionmentioning
confidence: 99%